Mendeley Application Training to Improve Students' Academic Writing Competence - Astri, Zul; Fachrunnisa, Nurul; Wahab, Isnaeni; Aisyah, Sitti; Nuraeni, Nuraeni; Misnawati, Misnawati (Sarana Ilmu Indonesia (salnesia), 2025)
Academic writing is an essential competence for students in supporting their academic success and scientific development. One of the common challenges faced is the proper and systematic management of references. This community service activity was aimed at providing training on the use of the Mendeley application for students of Universitas Muslim Maros, particularly those from the Faculty of Teacher Training and Education, to enhance their skills in managing scientific references. The training was conducted online via the Zoom platform on May 12, 2025, at 10:00 WITA, with a total of 133 registered participants. The evaluation results showed that approximately 93,4% of participants reported acquiring new skills that are highly useful for writing their final projects and other scientific papers. This activity is expected to serve as a solution for strengthening students' academic literacy in the digital era.